Mechanisms for overcoming socio-cultural gap and falsifications in the international environment of student youth - V. V. Bondarenko; E. V. Kuznetsova (Вестник университета, 2023)
The article studies mechanisms of counteracting falsification of consciousness and tools influencing constructive civic position of young people in the Russian higher education system. The determining role in this process is played by activities of Russian higher education institutions creating conditions for forming active citizenship of young people in the framework of educational, in-class, and extracurricular activities. The scientific research results obtained can be used by management of higher educational organizations in order to improve effectiveness of work in the field of organizing educational, inclass, and extracurricular activities in the process of forming active citizenship and implementing the national concept of state youth policy and patriotic education. The results allow expanding application of practices to overcome socio-cultural gap and falsifications in the international environment of student youth.